1993
DOI: 10.1177/140349489302100212
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and Neglect of The Elderly – a Nordic Perspective Report from a Nordic Research Project

Abstract: This article describes how abuse and neglect of the elderly was made an issue for research in a Nordic perspective. The Council of Nordic Ministers funded a cooperation between Nordic researchers on the issue of abuse of the elderly, based on a Norwegian initiative in 1988. The aim was to establish a base of knowledge in order to recommend social and political measures for each country. The researchers were chosen from the disciplines of social work, social anthropology, sociology, nursing sciences and medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…We assume that these reasons could also be valid for the elderly individuals who participated in our study. In community-based studies in the U.S.A., the prevalence of elder abuse (2-10%) is similar to that found in Canada (4%) and in northern Europe (1-8%), but higher than in our study (Podnieks, 1992;Hydle, 1993;Thomas, 2002). In developing countries, lower estimates related to elder abuse are reported.…”
Section: Discussionsupporting
confidence: 79%
“…We assume that these reasons could also be valid for the elderly individuals who participated in our study. In community-based studies in the U.S.A., the prevalence of elder abuse (2-10%) is similar to that found in Canada (4%) and in northern Europe (1-8%), but higher than in our study (Podnieks, 1992;Hydle, 1993;Thomas, 2002). In developing countries, lower estimates related to elder abuse are reported.…”
Section: Discussionsupporting
confidence: 79%
“…The finding is also is in line with other studies conducted in India, which demonstrated that 41% of male and 43% of female were reported to be victimized for the abuse, by their son [10]. Another study from Chennai, India revealed that Family members were the most common perpetrators of elderly and hence family support is significant factors associated with elder abuse [17][18][19]. Our findings are consistent with findings from similar studies indicating that the daughter-in-law is the primary perpetrator of elderly abuse followed by the son [20][21][22].…”
Section: Discussionsupporting
confidence: 88%
“…Lachs and others linked an established research cohort of 2812 community-dwelling older adults in New Haven with protective service records (12) and reported a 9-year prevalence of protective service referral for elder abuse of 1.6% (13). In Denmark, Finland, and Sweden, Hydle reported a 1% to 8% prevalence of abuse by close relatives (14). In the Netherlands, Comijs and others (15) reported a 1-year abuse prevalence of 5.6% in a random sample of 1797 elderly persons living independently in Amsterdam, with 3.2% verbal aggression, 1.4% financial abuse, 1.2% physical aggression, and 0.2% neglect (15).…”
Section: Prevalencementioning
confidence: 99%